How Does Courtroom Broadcasting Influence Public Confidence in Justice? The Mediation Effect of Vicarious Interpersonal Treatment - Xu, Jian; Liu, Cong (Frontiers in Psychology, 2020)
The present study aimed to examine whether the applied practice of cameras in courtrooms plays a positive role in public confidence in legal authorities and how such impact may occur from the perspectives of the Group Value Model and the surrogacy effect. A convenience sample of 170 college students participated in this experiment. The control group read the written judgment of a civil case published online while the experimental group read the same judgment and watched the court trial video of that case. The overarching mediation model confirmed that there was a significant and indirect influence of video watching on confidence in justice in general. The key underlying mechanisms of this impact were the positive perception of the interpersonal treatment by the judge as well as the perceived fairness of the procedure. This study contributes to the currently limited research examining whether and, if so, how courtroom broadcasting promotes public trust through obtaining empirical evidence. It also expands the application of the Group Value Model to a vicarious interaction setting and provides evidence of the surrogacy effect in a civil legal context.